AB0557 Long Term Neurodevelopmental Outcome in Children Born to Mothers with Antiphospholipid Antibodies During Pregnancy. (9th June 2015) - Nalli, C.; Iodice, A.; Andreoli, L.; Lojacono, A.; Motta, M.; Fazzi, E.; Tincani, A.
Abstract : Background: Antiphospholipid antibodies (aPL), hallmarks of antiphospholipid syndrome (APS), are described in about 30% of systemic lupus erythematosus (SLE) patients and, in a lesser extent, in other systemic autoimmune diseases (SAD). It is known the possible detrimental effect of aPL on pregnancy outcome since these conditions generally affect young women. A relationship between aPL and neurological manifestations has also been described in the frame of APS.On the contrary, the long-term neuropsychological outcome of children (chl) born to patients with aPL has been less investigated. Objectives: To evaluate the neurodevelopmental long-term outcome in chl exposed to maternal aPL during the third trimester of pregnancy. Methods: We enrolled 40 chl (median age 7.4 years, range 3-18; 19 female, 21 male) born to 32 women with SAD and aPL positivity during third trimester of pregnancy. In our cohort of 40 pregnancies, 21 mothers (53%) displayed triple aPL positivity, 11 (30%) double, 8 (16%) single. 11 out of the 16 SLE pregnancies occurred in patients with anti ds-DNA antibodies, while anti-Ro/SSA were always negative.A neurological physical exam was performed by a pediatric neurologist in all children.The Child Behavior Check List (CBCL) and a home-made questionnaire focusing on maternal drugs during pregnancy, gestational age, baby developmental milestones, scholastic performances were submitted to all mothers. Intellectual functioning were assessed by Wechsler scale for corrected age. We also performed the NEPSY-II (Developmental NEuroPSYchological Assessment) when indicated. Results: All chl, when evaluated, displayed normal neurological physical exam and intelligence level.We found mild problems in 13 chl (32.5%). The maternal and delivery characteristics are showed in the table . 11 chl were found with discrepant cognitive profile (verbal intelligence quotient >or< performance intelligence quotient) and sleep disorders. These chl were also studied with NEPSY and 2 showed pathological results in one or more of the examined area; therefore both chl were diagnosed with learning disabilities and both were preterm, one from SLE-mother anti-dsDNA neg and single aPL pos, the other from APS-mother triple aPL pos). 4 chl (10%) had a history of seizures and 2 out of them belonged to the group with discrepant cognitive profile: 1 of them was preterm and had neonatal stroke. Conclusions: Minor neurological disorder can be found in chl exposed to aPL in utero. Notably, we have found 4 epileptic chl (10%); this frequency results about 20 times higher than that of normal population. It is difficult to say if these findings are due to prematurity, to maternal disease or to environmental factors because we could not find a significant relationship with any of the investigated variables. However our results underline the importance of a careful follow-up of chl born to patients with aPL in order to support the needs of a growing child. References: Bomba M, et al. Neuropsychiatric aid in children born to patients with rheumatic diseases. Clin Exp Rheumatol 2010 Sep-Oct;28(5):767-73. Mekinian A, et al. Mothers' antiphospholipid antibodies during pregnancy and the relation to offspring outcome. Clin Exp Rheumatol 2014 May-Jun;32(3):446. Disclosure of Interest: None declared